2023
DOI: 10.1021/jacs.2c12034
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of Non-Centrosymmetric Hybrid Halide Perovskites

Abstract: Structural non-centrosymmetry in semiconducting organic–inorganic hybrid halide perovskites can introduce functionalities like anomalous photovoltaics and nonlinear optical properties. Here we introduce a design principle to prepare Pb- and Bi-based two- and one-dimensional hybrid perovskites with polar non-centrosymmetric space groups. The design principle relies on creating dissimilar hydrogen and halogen bonding non-covalent interactions at the organic–inorganic interface. For example, in organic cations li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 78 publications
1
40
0
Order By: Relevance
“…Figure S11 shows no difference in the dark current and photocurrent of (4,4′-EDP)Pb 2 Br 6 when illuminated with a 365 nm LED source with a power of 2 mW/cm 2 . Sometimes, the use of organic dications reduces the distance between inorganic layers of 2D perovskites, improving the charge transport between adjacent layers. In the comparison presented here, both (4,4′-VDP)Pb 2 Br 6 and (4,4′-EDP)Pb 2 Br 6 have organic dications of very similar lengths, ensuring a similar distance between the 1D inorganic sublattice. However, only one sample, (4,4′-VDP)Pb 2 Br 6 , shows photoconductivity, and the other does not.…”
supporting
confidence: 90%
“…Figure S11 shows no difference in the dark current and photocurrent of (4,4′-EDP)Pb 2 Br 6 when illuminated with a 365 nm LED source with a power of 2 mW/cm 2 . Sometimes, the use of organic dications reduces the distance between inorganic layers of 2D perovskites, improving the charge transport between adjacent layers. In the comparison presented here, both (4,4′-VDP)Pb 2 Br 6 and (4,4′-EDP)Pb 2 Br 6 have organic dications of very similar lengths, ensuring a similar distance between the 1D inorganic sublattice. However, only one sample, (4,4′-VDP)Pb 2 Br 6 , shows photoconductivity, and the other does not.…”
supporting
confidence: 90%
“…For a decade, lead halide perovskites (LHPs) have been promising candidates for light-harvesting materials. Their high absorption coefficient, low exciton binding energy, and long charge carrier diffusion lengths with a high defect tolerance factor are reasons for the rapid success of LHP nanocrystals (NCs) in photovoltaics. However, the complex surface chemistry due to the dynamic ligand shells and the colloidal instability in polar solvents restrict their true potential as photocatalysts. , Even though the photophysical properties emerge from the inorganic core, the surface ligands play a decisive role in enhancing the photocatalytic attributes of LHPs. Recent studies exploring the ligand chemistry of LHP NCs have highlighted the important aspects of functional ligands, which were, until now, merely regarded as capping agents. This includes (i) suppressing the non-radiative recombination processes by passivating the surface defects, (ii) refining the interplay of forces and surface interactions to improve the electron–hole extraction at the interface, , and (iii) introducing chirality to the LHPs. Following the seminal work by Protesescu et al, controlling the size and shape of the LHP NCs has been possible. However, the ligands employed as capping agents majorly include long-chain oleyl amine/oleic acid (OAm/OAc) dispersed in organic solvents, inhibiting charge transport due to their insulating nature.…”
Section: Post-synthetic Ligand Exchange (Psle) Strategymentioning
confidence: 99%
“…DFT calculations by Gebhardt et al showed that the electronic structure of the layered bulk phase of PEA 2 PbI 4 is almost unaffected by reducing the dimensionality to a monolayer, suggesting weak interactions between the molecular and perovskite sublattices along the stacking direction. The interaction between these sublattices was shown to be governed by steric effects in a study by Du et al Furthermore, polar structural distortions leading to chirality or Rashba-/Dresselhaus effects have been achieved through targeted templating with organic molecules. …”
Section: Introductionmentioning
confidence: 99%